A cross-sectional survey of emergency and essential surgical care capacity among hospitals with high trauma burden in a Central African country. Issue 1 (June 2015) - Kouo-Ngamby, Marquise; Dissak-Delon, Fanny; Feldhaus, Isabelle; Juillard, Catherine; Stevens, Kent; Ekeke-Monono, Martin
Abstract Background As the overwhelming surgical burden of injury and disease steadily increases, disproportionately affecting low- and middle-income countries, adequate surgical and trauma care systems are essential. Yet, little is known about the emergency and essential surgical care (EESC) capacity of facilities in many African countries. The objective of this study was to assess the EESC capacity in different types of hospitals across Cameroon. Methods This cross-sectional survey used the WHO Tool for Situational Analysis to Assess EESC, investigating four key areas: infrastructure, human resources, interventions, and equipment and supplies. Twelve hospitals were surveyed between August and September 2009. Facilities were conveniently sampled based on proximity to road traffic and sociodemographic composition of population served in four regions of Cameroon. To complete the survey, investigators interviewed heads of facilities, medical advisors, and nursing officers and consulted hospital records and statistics at each facility. Results Seven district hospitals, two regional hospitals, two general hospitals, and one missionary hospital completed the survey. Infrastructure for EESC was generally inadequate with the largest gaps in availability of oxygen concentrator supply, an on-site blood bank, and pain relief management guidelines. Human resources were scarce with a combined total of six qualified surgeons, seven qualified obstetrician/gynecologists, and no anesthesiologists at district, regional, and missionary hospitals. Of 35 surgical interventions, 16 were provided by all hospitals. District hospitals reported referring patients for 22 interventions. Only nine of the 67 pieces of equipment were available at all hospitals for all patients all of the time. Conclusions Severe shortages highlighted by this survey demonstrate the significant gaps in capacity of hospitals to deliver EESC and effectively address the increasing surgical burden of disease and injury in Cameroon. This data provides a foundation for evidence-based decision-making surrounding appropriate allocation and provision of resources for adequate EESC in the country.